The short version of the Indonesian falls efficacy scale for older adults - Raditya Kurniawan Djoar; Anastasia Putu Martha Anggarani; Rachmah Indawati; Wiwin Hendriani (Physical Therapy Journal of Indonesia, 2025)
Introduction: The short version of the falls efficacy scale–international (FES-I), consisting of seven items, has not yet been adapted for use in Indonesia, although the long version has been validated in Bahasa Indonesia. This study aimed to adapt and validate the Indonesian short version of the FES-I for use in time-limited settings or with frail older adults. Methods: This cross-sectional study validated the Indonesian Falls Efficacy Scale for older adults through translation, cultural adaptation, expert review, and reliability testing. Content validity was assessed by seven experts, and a field test was conducted with 135 older adults. Data were analyzed using Cronbach’s Alpha in IBM SPSS Statistics 26. Results: Among the 135 respondents, the majority (82%) were aged between 60 and 74 years, with females comprising 60% of the sample. The shortened questionnaire demonstrated good reliability (Cronbach’s Alpha = 0.8) and excellent validity (item content validity index= 0.857–1; scale-level content validity index= 0.938). Conclusion: The findings support the reliability and validity of the short Indonesian version of the FES. This version is especially effective and practical for quickly screening older adults with a fear of falling during daily activities and social interactions.